The epidemiological profile of women screened for precancerous cervical lesions at Benjamin Ngoubou Regional Hospital in Tchibanga, Gabon - Ledaga, Nathalie Ambounda; Woromogo, Sylvian Honore; Yagata-Moussa, Felicite-Emma; Mihindou, Astride Smeige; Simo Tekem, Vicky Noel; Kouanang, Alain Jepang (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cervical cancer is the second most common cancer after breast cancer, with about 528,000 new cases reported per year. This study aimed at determining the epidemiological profile of women screened for precancerous cervical lesions in the region of Tchibanga, Gabon. Methods: A descriptive cross-sectional study was conducted with 144 women as sample for study Using Statistical Package for social sciences (SPSS) software version 20.0, the socio-demographic, epidemiological characteristics and gynaeco-obstetrical history of the participants were obtained and presented by simple frequencies. The relative socioeconomic status of screened females was measured using the simplified calculation of the socio-economic position index. Results: The under 25 age group accounted for 32%. Non-menopausal women accounted for 86.8% and menopausal women 13.2% in the sample in this study. Women with at least 3 partners accounted for 88.3% of participants diagnosed with dysplasia. Participants with chlamydia accounted for 53.2% of women diagnosed with Cervical Intraepithelial Neoplasia (CIN). Multigestures and large multigestures accounted for 70.6% of participants with dysplasia. The prevalence of precancerous states was 11.8%, classified into CIN 1/condylomas, CIN 2 and CIN 3/CIS. Conclusions: Making screening a regular activity is important. Awareness-raising sessions on the benefits of screening and the fight against sexually transmitted diseases should be conducted, as well as the early treatment of Chlamydia infections.